Implementation of Loose Parts Media to Improve Problem-Solving Skills of Children Aged 5–6 Years at TKK Regina Pacis Bajawa - Genoveva Meo; Andi Nafsia; Efrida Ita; Maria Yuliana Kua (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study aims to determine the effect of using loose parts media on the problem-solving abilities of children aged 5–6 years at TKK Regina Pacis Bajawa. This research employed a pre-experimental method with a qualitative data analysis approach. The research subjects consisted of 25 children from Class B Merah. Data collection techniques were carried out through observation and documentation of learning activities to obtain a comprehensive picture of the problem-solving processes demonstrated by children during play activities. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the analysis showed changes in children’s behavior after the implementation of loose parts media, particularly in their ability to identify problems, try various solution strategies, and solve problems more independently. Children appeared more active, creative, and demonstrated persistence when facing challenges during play. Thus, the use of loose parts media has a positive effect on improving the problem-solving abilities of children aged 5–6 years at TKK Regina Pacis Bajawa.